Pengaruh Biaya Produksi, Biaya Operasional dan Total Aktiva Terhadap Laba Bersih pada Perusahaan Garment dan Tekstil di Bursa Efek Indonesia Tahun 2018-2020 - Zauyah, Latifah (BISMA : Business and Management Journal, 2023)
This study aims to determine the partial and simultaneous effect of production costs, operational costs and total assets on net profit of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The data used in this study are secondary data in quantitative form obtained from annual financial reports published on the official website of the Indonesia Stock Exchange (www.idx.co.id). The population in this study are all textile and garment companies. The research sample was taken using purposive sampling method. From a population of 22 companies, 17 companies were obtained as samples. The data analysis method used is descriptive analysis, classical assumption test, multiple linear regression analysis and hypothesis testing. Based on the partial results of the study (t test) it shows that the variables of production costs and operational costs have a significant effect on net income because the sig value is 0.05 while total assets have no effect on net income. The results of the simultaneous study (f test) show that the variables of production costs, operational costs and total assets have a significant influence on stock returns. Calculation of the coefficient of determination (adjusted R square) shows that all independent variables, namely production costs, operational costs and total assets can explain the stock return variable of 0.27% while the remaining 99.73% is influenced by other variables not examined in this study.